About General Philosophical Methods of Knowledge of Legal Phenomena and Processes - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2022)
In this scientific article, emphasizing the special importance in the studies of law of general philosophical methods that determine the content of the methodology as a whole, the method of existentialism is considered as one of them, which is analyzed in great detail from the standpoint of its supporters, and is also critically evaluated by modern scientists.